"All Parties Treat Silesians Instrumentally": On Political Representation at the Regional Level. Issue 2 (20th March 2022) - Turska-Kawa, Agnieszka; Glajcar, Rafał
Abstract: The turn of the 20th century experienced an intensification of processes that strengthened Silesian identity, which became an important element of political debate in the region. This was reflected in the emergence of a growing number of entities that placed Silesian issues among their priority objectives and defined themselves as representatives of the interests of Silesia and Silesians. The aim of the study was to verify the political representative potential of groups in Upper Silesia. We accepted the hypothesis that the stronger the identity of a particular group (regional or national) the greater the probability that entities placing fundamental objectives strictly within the scope of regional issues should enjoy broad support in the region, and such entities consequently should be perceived as political representatives of the group. A study conducted using the categorized interview method (N=54) proves quite clearly that Silesians are unable to identify entities on the regional political scene that could represent them sufficiently. The determinants of this state of affairs are found not only in the negative actions of political entities but also in the absence of a clear vision of representation, which could constitute a basis for the formulated expectations of Silesians.